2017
DOI: 10.1242/dev.157404
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of gene regulation in human embryos and pluripotent stem cells

Abstract: Pluripotent stem cells have broad utility in biomedical research and their molecular regulation has thus garnered substantial interest. While the principles that establish and regulate pluripotency have been well defined in the mouse, it has been difficult to extrapolate these insights to the human system due to species-specific differences and the distinct developmental identities of mouse versus human embryonic stem cells. In this Review, we examine genome-wide approaches to elucidate the regulatory principl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 173 publications
0
47
0
Order By: Relevance
“…We present the first pluripotent stem cell model permitting assessment of the consequences of selective genetic p110α activation specifically in a human developmental context. This is important given the well-documented differences between the pathways regulating mouse and human stem cell pluripotency and differentiation (51). By using CRISPR-mediated knock-in of PIK3CA H1047R into one or both endogenous PIK3CA alleles, we were able to examine the importance of mutant PIK3CA allele dosage for pathway activation and downstream cellular responses.…”
Section: Discussionmentioning
confidence: 99%
“…We present the first pluripotent stem cell model permitting assessment of the consequences of selective genetic p110α activation specifically in a human developmental context. This is important given the well-documented differences between the pathways regulating mouse and human stem cell pluripotency and differentiation (51). By using CRISPR-mediated knock-in of PIK3CA H1047R into one or both endogenous PIK3CA alleles, we were able to examine the importance of mutant PIK3CA allele dosage for pathway activation and downstream cellular responses.…”
Section: Discussionmentioning
confidence: 99%
“…Human pluripotent stem cells (hPSCs) provide a powerful alternative since they can proliferate almost indefinitely while maintaining the capacity to differentiate efficiently into the three germ layers (8). Thus, hPSCs have been used to uncover mechanisms directing germ layer specification (9)(10)(11). Of particular interest, studies have shown key functions for the cell cycle machinery in the specification of endoderm versus ectoderm and exist from the pluripotent state.…”
mentioning
confidence: 99%
“…phLIF thus appeared to be active, with a similar effect to commercial LIF. To further confirm phLIF activity, we analyzed mRNA levels of the mouse transcription factors, Oct4, Sox2, and Nanog, which are pluripotency markers (Theunissen & Jaenisch, 2017). mESCs cultured in the presence of phLIF or commercial LIF showed significantly elevated expression of all three genes compared to those cultured without LIF ( Figure 6B).…”
Section: His:hlif Produced In Plants Contains Low Levels Of Endotoxinmentioning
confidence: 99%